INNOVATIVE MARKETING APPROACHES TO MANAGING THE COMPETITIVENESS OF ENGINEERING COMPANIES - Kolesnyk, Dmytro V.; Miahkykh, Iryna M. (Journal of Strategic Economic Research, 2025)
The article investigates contemporary innovative marketing approaches to managing the competitiveness of engineering companies in the context of the digital transformation of the economy. The specificity of engineering services, characterized by a high level of intellectualization, project individualization, and complexity of implementation, which limits the effectiveness of traditional marketing tools, is analyzed. It is shown that the integration of digital technologies, big data analytics, CRM systems, online platforms, and personalized value propositions enhances the effectiveness of marketing communications, strengthens long-term customer relationships, and forms sustainable competitive advantages. The role of customer-oriented and integrated marketing, which aligns marketing activities with production and management processes of the enterprise, is examined. A model for managing the competitiveness of engineering companies is proposed, which combines market analysis, strategic planning, digital tools, customer relationship management, and evaluation of marketing performance. The model demonstrates the sequence of key stages and the interconnection of blocks, ensuring cyclical improvement of the system and increasing the adaptability of the business model to changes in the market environment. The article emphasizes the importance of analytical methods for evaluating the effectiveness of marketing strategies, which allows companies to make informed management decisions, optimize processes, and forecast the dynamics of competitive advantages. Special attention is paid to the adaptation of marketing tools to the specifics of intellectual services, enhancing customer interaction, and implementing innovative practices in business processes, ensuring stable market positioning and long-term growth of competitiveness. The scientific novelty of the article lies in a comprehensive approach to integrating innovative marketing strategies, digital technologies, and customer-oriented practices, enabling engineering companies to effectively respond to the challenges of the modern competitive environment and develop long-term competitive advantages.